Draft Fifth Five Year Plan of Andaman and Nicobar Islands (1974-79) (Volume 1) - Planning Commission (Planning Commission, 1974)
The Andaman and Nicobar Islands constitute a single District Union Territory without legislature. This territory is administered by the President of India through the Chief Commissioner. The present Chief Commissioner is Shri Har Mander Singh, I.A.S. The Development Commissioner-cum-Development Secretary of this Administration is Shri S.C. Borah, I.F.A.S. The geographical situation of these islands is between 6° and 14° North latitude and 92° and 94° East longitudes.
Andaman and Nicobar Administration